PENGARUH DANA PIHAK KETIGA, PENGELOLAAN KREDIT, PENGELOLAAN LIKUIDITAS, DAN EFISIENSI OPERASI TERHADAP PROFITABILITAS BANK GO PUBLIC YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014 - Samsul Anwar (Universitas Pamulang, 2018)
Indonesian banking conditions slowed in line with the moderation in domestic economic slowdown. There are several factors, among others: The Deposits, Credit Management, Liquidity Management and the Operating Efficiency. This study aims to examine and analyze the influence of the Deposits, the Manage of Loans, the Manage of Liquidity and the Operating Efficiency towards Profitability at Bank Go Public listed on the Indonesian Exchange Stocks Period 2010-2014. The research data is annual report for the observation period 2010-2014. The sampling method used was purposive sampling. The analytical method used in this research is the method of Common Effect. The results and conclusions showed that the Deposits, the Manage of Loans, the Manage of Liquidity, and the Operating Efficiency simultaneously are having significant influence to the Proftability of Go Public Banks Listed in Indonesian Exchange Stocks. Partially the Deposits and the Operating Efficiency are having influence on the Proftability of Go Public Banks Listed in Indonesian Exchange Stocks. While the Manage of Loans and the Manage of Liquidity are not having significant influence on the profitability.Keywords: The Deposits, the Manage of Loans, the Manage of Liquidity, the Operating Efficiency, Profitability.